Developing algae as a sustainable food source - Diaz, Crisandra J.; Douglas, Kai J.; Kang, Kalisa; Kolarik, Ashlynn L.; Malinovski, Rodeon; Torres-Tiji, Yasin; Molino, João V.; Badary, Amr; Mayfield, Stephen P. (Frontiers in Nutrition, 2023)
The challenges posed by an increasing population, coupled with the impacts of climate change on our existing agricultural production, are causing worldwide concerns about our ability to feed future generations without causing significant environmental degradation. Agricultural crops currently face the problems of inefficient land, nutrient, and water usage, with limited potential to expand agriculture production in most parts of the world. In contrast, microalgae and cyanobacteria (which we will refer to simply as “algae”) have evolved to be highly efficient at resource utilization and have proven to be a viable source of nutritious biomass that could address many of the current traditional food production issues. Algae are photosynthetic microorganisms that are able to grow through the consumption of carbon dioxide, light, and nutrients, and can be produced on non-arable land using non-potable water, including brackish or seawater. This means that algae will complement rather than compete with traditional agriculture. Algae have proven particularly capable of displaying the desired qualities of a sustainable food source because they produce highly digestible proteins, lipids, and carbohydrates, and are rich in essential fatty acids, vitamins, and minerals. Although they have yet to be fully domesticated as food sources, there are currently tools available, including breeding and genetic manipulation, that will allow for increasing the productivity and nutritional quality of algal strains. The culmination of this domestication process will allow commercial production of algae as a new “super food”, and realizing this goal is well within our reach. Here, we highlight the current advancements that will expand the variety of algae-based nutritional sources, as well as outline various challenges between current biomass production and large-scale economic production of algae for the food market.